Interpersonal Communication Strategies of Marriage Registrars in Consultation: Strategi Komunikasi Antarpribadi Penghulu dalam Konsultasi Pernikahan - Haris, Ismail; Mahmuddin, Mahmuddin; Anshar, Muhammad; Hamiruddin, Hamiruddin; Noer, Usman (Academia Open, 2026)
General Background: Marriage harmony requires effective interpersonal communication, particularly amid increasing household conflicts in urban communities. Specific Background: The Religious Affairs Office (KUA) in Biringkanaya Makassar provides marriage consultation services where registrars (penghulu) act as mediators through structured communication. Knowledge Gap: Studies have rarely examined the specific interpersonal communication strategies of penghulu in practical consultation contexts. Aims: This study analyzes communication stages, forms, supporting factors, and obstacles in marriage consultation. Results: Findings show a staged process consisting of building trust, exploring problems, clarifying and reflecting issues, and facilitating solutions and commitments. Communication forms include persuasive verbal, empathetic nonverbal, and religious symbolic communication. Supporting factors involve registrar credibility, institutional legitimacy, and alignment with religious values, while obstacles include emotional instability, cultural and educational differences, and limited time. Novelty: The integration of empathetic communication with religious values emerges as a key strategy to foster openness and resolve domestic conflicts. Implications: The study contributes to interpersonal communication theory and provides practical guidance for improving marriage consultation services in religious institutions. Highlights• Structured stages guide consultation toward shared solutions• Combined communication forms address emotional and cognitive aspects• Value-based interaction supports conflict resolution KeywordsInterpersonal Communication; Communication Strategy; Marriage Consultation; Religious Institutions; KUA